Domestic value added and employment generated by Chinese exports: A quantitative estimation - Chen Xikang; Leonard K. Cheng; K. C. Fung; Lawrence J. Lau; Yun Wing Sung; C. Yang; K. Zhu; J. Pei; Z. Tang (University of California, Santa Cruz Institute for International Economics (SCIIE), 2008)
We develop an input-output methodology to estimate how Chinese exports affect the country's total domestic value added (DVA) and employment for 1995 and 2002. Total DVA generated by exports is obtained by subtracting all direct and indirect imported intermediate goods from the gross value of exports, and total employment is obtained by adding all direct and indirect employment generated by exports. To implement these estimations, we use hither to unpublished Chinese government data to construct several completely new datasets, including an input-output table with separate input-output and employment-output coefficients for processing and non-processing exports. In 2002 (1995), for every US1,000 dollar of Chinese exports, DVA and employment are estimated to be US466 (US545) and 0.242 (0.375) person-year, respectively.
Keywords: 330